Colchicine as an Adjuvant Therapy for Coronary Artery Disease: A Systematic Review - Nobian Andre; Patricia Renata; Muhamad Hafiz Mahruzza; Rony Marethianto Santoso (The Indonesian Heart Association, 2020)
Background:Inflammation plays a significant role in atherosclerosis at all phases. Colchicine is a pleiotropic anti-inflammatory agent that may be beneficial in various stages of coronary artery disease (CAD). Methods:We searched for literatures in PubMed, Cochrane Library, ScienceDirect, and Proquest regarding the use of colchicine on top of current optimal medical therapy for CAD. Results: Twelve studies were identified: three studies in stable CAD patients and the remaining nine assessed in acute coronary syndrome (ACS) and post-ACS patients. The majority of studies used a colchicine dose of 0.5 mg/day. Adjuvant colchicine of 0.5 mg daily reduced the risk of developing ACS, cardiac arrest, or ischemic stroke in stable CAD: HR (hazard risk) 0.33 (95% CI 0.18-0.59), p<0.001. Patients admitted with ACS who received a 2 mg loading dose of colchicine pre-percutaneous coronary intervention (PCI) showed smaller infarct size than control: 18.3 (IQR 7.6-29.9) ml/1.73 m2vs 23.2 (18.5-33.4) ml/1.73 m2(p=0.019).In post-ACS patients, adjuvant colchicine of 0.5 mg daily significantly reduced the rate of ischemic cardiovascular events: HR 0.77 (95% CI 0.61-0.96), p=0.02. Conclusion: Stable CAD patients benefit from 0.5 mg daily dose of adjuvant colchicine to reduce the incidence of future cardiovascular events. For patients presenting with ACS, a loading dose of 2 mg of colchicine pre-PCI followed by a week of 0.5 mg colchicine twice daily on top of optimal medical care can reduce infarct size. This should be followed by consumption of 0.5 mg daily dose of adjuvant colchicine post-ACS for at least 20 months to prevent future reinfarctions.